2018
DOI: 10.3847/1538-3881/aaa54e
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Planet Detections with Near-infrared Radial Velocities in the Upcoming SPIRou Legacy Survey-planet Search

Abstract: The SPIRou near infrared spectro-polarimeter is destined to begin science operations at the CanadaFrance-Hawaii Telescope in mid-2018. One of the instrument's primary science goals is to discover the closest exoplanets to the Solar System by conducting a 3-5 year long radial velocity survey of nearby M dwarfs at an expected precision of ∼ 1 m s −1 ; the SPIRou Legacy Survey-Planet Search (SLS-PS). In this study we conduct a detailed Monte-Carlo simulation of the SLS-PS using our current understanding of the oc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 136 publications
0
10
0
Order By: Relevance
“…We do not show planets beyond P = 3000 d, as our N-body integration time of 20 Myr is too short to account for their large growth timescales. We also exclude objects smaller than 0.5 R ⊕ , which are not observable with state-of-the-art exoplanet detection techniques (e.g., Dumusque et al 2011;Cloutier et al 2018;Reiners et al 2018;Bryson et al 2020;Trifonov et al 2020). The majority of planets are of terrestrial size and reside on intermediate or wide orbits.…”
Section: Results: Synthetic Populationmentioning
confidence: 99%
“…We do not show planets beyond P = 3000 d, as our N-body integration time of 20 Myr is too short to account for their large growth timescales. We also exclude objects smaller than 0.5 R ⊕ , which are not observable with state-of-the-art exoplanet detection techniques (e.g., Dumusque et al 2011;Cloutier et al 2018;Reiners et al 2018;Bryson et al 2020;Trifonov et al 2020). The majority of planets are of terrestrial size and reside on intermediate or wide orbits.…”
Section: Results: Synthetic Populationmentioning
confidence: 99%
“…We do not show planets beyond P = 3000 d, as our N-body integration time of 20 Myr is too short to account for their large growth timescales. We also exclude objects smaller than 0.5 R ⊕ , which are not observable with state-of-the-art exoplanet detection techniques (e.g., Dumusque et al 2011;Cloutier et al 2018;Reiners et al 2018;Bryson et al 2019;Trifonov et al 2020). The We exclude planets smaller than 0.5 R ⊕ and with periods beyond 3000 d. The radius frequencies follow a distinct bimodal distribution with the bulk at its low-size end.…”
Section: Occurrence Ratesmentioning
confidence: 99%
“…Weiss et al 2013;Rogers 2015;Wolfgang et al 2016) is an important step towards understanding the diversity of exoplanet compositions as well as its use as a tool in predictive studies (e.g. S15; Cloutier et al 2017a, Cloutier et al 2018. For example, consideration of small exoplanets (r p ≤ 4 R ⊕ ) with masses measured to better than 20% revealed that a large fraction of planets with r p 1.6 R ⊕ are rocky with bulk compositions consistent with that of the Earth and Venus .…”
Section: A-priori Estimate Of the 'Best' Targetsmentioning
confidence: 99%